Status Of Sucking Insect Pests And Yellow Mosaic Disease Incidence In Major Greengram, (Vigna Radiata) Growing Districts Of Karnataka - S. Ambarish; C. M. Kalleshwaraswamy; V. Venkataravanappa (International Journal of Insects, 2024)
Yellow Mosaic Disease (YMD) and sucking insect pests are the serious problem to greengram growing farmers in Karnataka. Information on the regional distribution of vectors involved and the disease transmitted is essential to manage the pests. In the present study, roving survey was undertaken during Kharif season of 2018 and 2019 in eight major greengram growing districts of Karnataka. The species of sucking pests observed on green gram are whitefly, Bemisia tabaci Asia-I group, aphids, Aphis craccivora and leafhopper, Empoasca kerri. There was a variation in pest incidence and also YMD incidence across the districts surveyed. The results indicated that whitefly population ranged from 1.08 to 4.23 per trifoliate leaf. The maximum numbers of whitefly population (4.23/trifoliate leaf) and YMD incidence (68.75%) was recorded in Belagavi district and the lowest number of whiteflies (1.08/trifoliate leaf) and YMD (10.32%) was observed Shivamogga district. The highest number of leafhoppers (5.32/trifoliate leaf) and aphids (57.62/ 5 cm twig) were observed in Chitradurga and Davanagere districts, respectively. High incidence of YMD is linked to high activity of sucking pests especially whiteflies which are reported vectors. Incidence was high in greengram was grown as sole crop than mixed crop. The variation in sucking insect pests and YMD incidence in greengram was discussed in this paper. The result may also help to develop the management strategies for the pests and diseases combined.
Keywords: Aphids; YMD; disease incidence; leafhoppers; roving survey; whiteflies